Automatic 3D reconstruction of tumor using 2D H&E images - Ho, Adriel Jin Liang (Nanyang Technological University, 2021)
The analysis of normal and disease processes, especially when it involves structural changes or those in which the spatial relationship of disease features is significant, could benefit greatly from three-dimensional (3D) reconstruction and analysis of tissue at microscopic resolution. However, the process of 3D reconstruction is challenging because the solutions to produce an accurate model are often technical, complex, and time-consuming to learn. In this paper, we proposed an automatic 3D reconstruction method to reconstruct tumors from its Haematoxylin and Eosin (H&E) stained serial-sectioned tissues using the Python programming language to shield users from the difficult challenges that 3D reconstruction pose.